La taupe et le serpent. Discipline et contrôle dans les tribunaux pour enfants aux États-Unis (xxe-xxie siècles) - Guillaume Périssol (Transatlantica)
Because of their rehabilitative rationale, the juvenile courts created in the United States seek to know the delinquent and his environment. How has the study of younger people functioned and evolved, producing a “truth” that is affected by power relations? While probation has become the principal rehabilitation measure in the western penal system—even beyond juvenile justice—should we still be employing the disciplinary model? Furthermore, what remains of the disciplinary society described by Michel Foucault when he proposed the prison as the analogic model for the enclosed milieux used for containing people in modern times? Our hypothesis is that the invention of a probationary system to manage increasing numbers of deviants reveals a shift from disciplinary societies to societies of control, as envisaged by Gilles Deleuze in 1990.